Media Pembelajaran Anak Usia Dini dan Siswa Sekolah Dasar Berbasis Macromedia Flash 8 - Nuning Melianingsih (Politeknosains, 2018)
Most of lessons for children in a house or even in a school still use learning methods that use written module as a media. However, technology that is developed to be a reason to reduce the use of written learning media or module that is substituted by digital books. For students, learning digital books are more interested than written module because those can be more interactive to learn. Therefore, it is needed to develop a learning media that is liked by the students. Research method used is research and development. The steps in the research process are analysis, designs, developments, implementations, and testing. Testing is validity that is done by expert judgments. Then, media is tested by the students. After the implementation of validity and media meet the criteria, they are tested or investigated to know the feasibility in the field. This research is aimed to know the result of the development from educating calculated game and the introduction in the name of fruits and animals using macromedia Flash 8, to know the feasibility interactive calculated media and to know the name of fruits and animals as learning media to increase the learning result for elementary schools students grade 1 and early childhoods based macromedia flash, and to know the feasibility as a learning media. Therefore, it can be concluded that interactive calculated learning media and to know the name of fruits and animals can be used as learning media in learning process.